Total Oil Content and Fatty Acid Profile of some Almond (Amygdalus Communis L.) Cultivars - Yildirim Adnan Nurhan; Akinci-Yildirim Fatma; Şan Bekir; Sesli Yılmaz (Polish Journal of Food and Nutrition Sciences)
This study was conducted to determine the total oil contents and fatty acid compositions of some commercial almond cultivars. The total oil contents changed significantly (p<0.05) by year in all cultivars with the exception of cultivar Ferrastar. Total oil contents were changed from 50.90% (Picantili) to 62.01% (Supernova) in 2008 and from 52.44% (Lauranne) to 63.18% (Cristomorto) in 2009. While predominant unsaturated fatty acids were oleic and linoleic acids, predominant saturated fatty acid was palmitic acid. The highest amount of oleic acid was obtained in Glorieta in both 2008 (83.35%) and 2009 (72.74%). Linoleic acid content varied by year and the highest content was recorded in Picantili (26.08%) in 2008 and Yaltinski (30.01%) in 2009. The highest amount of palmitic acid was detected in cultivar Sonora in both years, i.e. as 7.76% in 2008 and 10.11% in 2009. The mean UFA:SFA ratio was 11.73 in 2008 but 7.59 in 2009. Principal component (PC) analysis indicated that palmitic acid, palmitoleic acid, stearic acid, oleic acid, arachidic acid, unsaturated fatty acid (UFA), saturated fatty acid (SFA) and UFA:SFA ratio were primarily responsible for the separation on PC1